Cancer epidemiology and prevention - Schottenfeld, David; Fraumeni, Joseph F. (New York ; Oxford : Oxford University Press, 2006)
Drawing widely from international sources, the new edition of this reference book on cancer causes, incidence, mortality and survival patterns, also includes chapters on social class, obesity, physical activity and chemoprevention plus other related topics in the field.
Previous ed.: 1996.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Cancer -- Prevention; Cancer -- Epidemiology